Perancangan Sistem Informasi Akuntansi Menggunakan Prototype Pada UMKM Depot Penggilingan Bakso Mas Rochim - Roshani, Roshani; Sentiya, Novi; Mukaromah, Lailatul (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Financial reports need to have qualitative characteristics that can support the level of quality and usefulness of the information they contain because they are used as a guide in decision making so that consumers of financial reporting can make correct judgments. The aim of this research is to design an accounting information system using the prototype method. The prototype model applied in this research method is Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, Depeloyment, Delivery & Feedback on how to get a representation of the accounting information system modeling that will be created. So the results of this research are ini the form of a web based accounting information system using a prototype to produce features in the form of account data, general journal, ledger, trial balance, profit and loss, Calk and report as required by UMKM.